ADRENAL ULTRASOUND - Diana Loreta Paun; Mara Carsote; Ana Velea; Ancuta Augustina Gheorghisan-Galateanu; Rucsandra Danciulescu-Miulescu; Adina Ghemigian (Romanian Journal of Medical Practice, 2019)
Ultrasound is the first step to detect an abdominal tumour at the level of adrenal. The most common scenario is related to the pelvic and abdominal ultrasound. This kind of tumour is more frequently seen in menopausal women than in premenopausal ones. We introduce a case of a menopausal woman accidentally detected at ultrasound with an adrenal mass starting from a routine gynaecological control. The use of ultrasound on adrenal masses is related to their detection and follow-up in cases when surgery is not necessary